2009
DOI: 10.1002/anie.200805193
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphorus Analogue of Bis(η4‐cyclobutadiene)iron(0)

Abstract: P makes it possible: The convenient oxidative synthesis of the 16-electron organophosphorus iron sandwich complex [Fe(eta(4)-P(2)C(2)tBu(2))(2)] (see structure) suggests that the elusive all-carbon complex [Fe(eta(4)-C(4)H(4))(2)] is a viable synthetic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 36 publications
2
21
0
3
Order By: Relevance
“…[10][11][12] Unambiguous distinction between homogeneous and heterogeneous catalysts is intricate, [21] yet our observations are consistent with a homogeneous mechanism. The loss of suitable p acceptors after complete hydrogenation of 1-dodecene (and 2 % anthracene from the precatalyst) resulted in catalyst precipitation.…”
Section: Angewandte Chemiesupporting
confidence: 79%
See 1 more Smart Citation
“…[10][11][12] Unambiguous distinction between homogeneous and heterogeneous catalysts is intricate, [21] yet our observations are consistent with a homogeneous mechanism. The loss of suitable p acceptors after complete hydrogenation of 1-dodecene (and 2 % anthracene from the precatalyst) resulted in catalyst precipitation.…”
Section: Angewandte Chemiesupporting
confidence: 79%
“…[6b,c] A PNP pincer ligand was recently used by Hanson and coworkers to stabilize a cobalt catalyst with 15 valence electrons that allowed hydrogenation of alkenes, ketones, and imines after activation by Brookharts acid. [10,11] Unlike many catalytic reactions where this scenario would entail catalyst aggregation and deactivation, the presence of a large excess of p-acidic ligands in hydrogenations (of unsaturated molecules such as alkenes, arenes, and carbonyl compounds) can effect rapid ligand exchange between p ligands and thus assure prolonged catalyst activity in the homogeneous phase. [8] The same research group reported high activities of bis(imino)pyridine-and bis(arylimidazol-2-ylidene)pyridine-iron and -cobalt catalysts bearing two labile N 2 ligands (Scheme 1).…”
mentioning
confidence: 99%
“…The recent discovery by Lammertsma and co-workers in 2008 of metal sandwich complexes of the diphosphacyclobutadiene ligands [4,6,7] makes of interest the structures and thermochemistry of related metal carbonyl derivatives. In this connection, the lowest energy (Me 2 C 2 P 2 ) 2 Fe 2 (CO) 5 structure is found to have one bridging g 1 ,g 4 -Me 2 C 2 P 2 ring as well as a terminal g 4 -Me 2 C 2 P 2 ring and an iron-iron distance of $4.3 Å far too long for a direct ironiron bond.…”
Section: Discussionmentioning
confidence: 99%
“…[5] This nickel sandwich has the favored 18-electron configuration and is particularly stable. More recently (2008) Lammertsma and coworkers have used the displacement of coordinated anthracene from the cobalt and iron [(g 4 -C 14 H 10 ) 2 M] À anions (M = Co, [6] Fe [7]) with four equivalents of Bu t C"P:to synthesize the anionic sandwich compounds [(g 4 -Bu t 2 C 2 P 2 ) 2 M] À . The corresponding neutral sandwich compounds (g 4 -Bu t 2 C 2 P 2 ) 2 M (M = Co, Fe) were then obtained by oxidation of these anions with (g 5 -C 5 H 5 ) 2 Fe + .…”
Section: Introductionmentioning
confidence: 99%
“…Aufbauend auf unsere bisherigen Arbeiten zur Eisen(‐I)‐ und Cobalt(‐I)‐vermittelten Phosphaalkindimerisierung, begannen wir vor kurzem, analoge Reaktionen von Phosphaalkinen mit Nickel(0)‐Verbindungen zu untersuchen. Bei der Reaktion von [Ni(CO) 4 ] mit einem Überschuss an t Bu‐C≡P (50 Äquivalente) zeigte das 31 P{ 1 H}‐NMR‐Spektrum der Reaktionslösung unerwartet ein hochfeldverschobenes Singulett bei −468.2 ppm neben dem Signal des freien t Bu‐C≡P bei −68.1 ppm.…”
Section: Figureunclassified